1995
DOI: 10.1002/macp.1995.021960531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ortho‐substituents on the living polymerization of phenylacetylenes by MoOCl4‐based catalysts

Abstract: Polymerization of phenylacetylenes (PAS) having various ortho-substituents were examined by using MoOCI,-n-Bu,Sn-EtOH (mole ratio 1 : 1 : 1) as catalyst. Phenylacetylenes with no or sterically small ortho-substituents did not polymerize in a living fashion. On the other hand, in the polymerization of phenylacetylenes having medium-sized substituents (e. g., CH,, C1, Br, and iPr), the number-average molecular weights M, of polymers increased in direct proportion to monomer consumption, while the polydispersity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Thus one can see that the MWD narrows with increase in the bulkiness of orthosubstituent. This tendency is the same as in previously developed systems such as toluene, 29 19 and MoOClcn-BuLi/anisole. 20 This means that steric effect of artha-substituents in phenylacetylene plays a vital role in achieving living polymerization by using Mo0Cl 4-based catalysts.…”
Section: Polymerization Of Other Acetylenessupporting
confidence: 86%
“…Thus one can see that the MWD narrows with increase in the bulkiness of orthosubstituent. This tendency is the same as in previously developed systems such as toluene, 29 19 and MoOClcn-BuLi/anisole. 20 This means that steric effect of artha-substituents in phenylacetylene plays a vital role in achieving living polymerization by using Mo0Cl 4-based catalysts.…”
Section: Polymerization Of Other Acetylenessupporting
confidence: 86%
“…Although the initiation efficiencies of 8b ‐mediated polymerizations of ortho‐substituted phenylacetylenes were usually around 10%, initiation efficiencies as high as 20–30% were observed when ortho ‐(trialkylsilyl)methylene groups of different steric demands were used as substituents 81. Interestingly, 8b even effected the controlled polymerization of ( o ‐isopropylphenyl)acetylene,57 ( o ‐methylphenyl)acetylene,83 ( o ‐bromophenyl)acetylene,84 ( o ‐chlorophenyl)acetylene,57 and ( p ‐ n ‐butyl‐ o,o,m,m ‐tetrafluorophenyl)acetylene,85 which bear sterically less demanding ortho substituents (Table 1). A comparison of the polymerization results of 8b ‐derived poly(phenylacetylene)s having various ortho substituents57, 84 confirmed the observations reported from Percec's group 76.…”
Section: Transition‐metal Halide‐basedinitiatorsmentioning
confidence: 99%
“…Interestingly, 8b even effected the controlled polymerization of ( o ‐isopropylphenyl)acetylene,57 ( o ‐methylphenyl)acetylene,83 ( o ‐bromophenyl)acetylene,84 ( o ‐chlorophenyl)acetylene,57 and ( p ‐ n ‐butyl‐ o,o,m,m ‐tetrafluorophenyl)acetylene,85 which bear sterically less demanding ortho substituents (Table 1). A comparison of the polymerization results of 8b ‐derived poly(phenylacetylene)s having various ortho substituents57, 84 confirmed the observations reported from Percec's group 76. Hence, sterically demanding ortho substituents are believed to be indispensable to produce sterically crowded propagating species in which chain transfer and termination are prohibited because of steric hindrance.…”
Section: Transition‐metal Halide‐basedinitiatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The living polymerization of substituted acetylenes has been achieved with Schrock carbenes, 1-5 MoOCl 4 -based ternary catalysts, 6 -8 and Rh catalysts. 9, 10 We have found that fairly many substituted acetylenes (e.g., 1-chloro-1-alkynes, 11 tert-butylacetylene, 12 and various ortho-substituted phenylacetylenes 13 ) polymerize in a living fashion in the presence of the MoOCl 4 -n-Bu 4 Sn-EtOH catalyst in a toluene solution. Except for 1-chloro-1-alkynes, however, there have been no examples of disubstituted acetylenes that polymerize in a living fashion with MoOCl 4 -based catalysts.…”
Section: Introductionmentioning
confidence: 99%